Review on Image Segmentation Techniques for Red Blood cell Identification - Taneja, Neeti; Kaur, Kamaljeet (International Journal of Computer Sciences and Engineering, 2025)
This review paper highlights the methodology followed for analysing the medical image by extracting the red blood cells from it. The image of blood cell sample is captured through microscope which consists of number of cells. Different techniques for segmentation of image such as edge detection, thresholding, Morphological processing etc. are used for the area evaluation of red blood cells for its efficient analysis. The main objective is to adopt the proposed methodology for discovering the red blood cells in the microscopic image.